Genetic association signal near NTN4 in Tourette Syndrome - Paschou, Peristera (2014)
Tourette Syndrome (TS) is a neurodevelopmental disorder with a complex genetic etiology. Through an international collaboration, we genotyped 42 single nucleotide polymorphisms (SNPs)(p<10(−3)) from the recent TS genome-wide association study (GWAS) in 609 independent cases and 610 ancestry-matched controls. Only rs2060546 on chromosome 12q22 (p=3.3×10(−4)) remained significant after Bonferroni correction. Meta-analysis with the original GWAS yielded the strongest association to date (p=5.8×10(−7)). Although its functional significance is unclear, rs2060546 lies closest to NTN4, an axon guidance molecule expressed in developing striatum. Risk score analysis significantly predicted case/control status (p=0.042), suggesting that many of these variants are true TS risk alleles.